Components of the Competitiveness of the Coastal Region (Economics and region, 2021)
The problems of determining the elements of competitiveness of coastal regions are considered. Theoretical generalization and comparison of elements of competitiveness according to the theories of A. Maslow (pyramid of needs and its interpretation on the competitiveness of the region), M. Porter (model 5 forces of competition) are carried out. The understanding of the mechanism of competitiveness of coastal regions as interaction of elements is offered: administration, territory, people and processes. The structure of competitiveness of coastal regions is described. It is noted that the specifics of coastal regions is to provide competitive infrastructure, tourist and recreational complex, a set of environmental and ecosystem measures.
Keywords: competitiveness of the region; coastal region; elements of competitiveness; structure of competitiveness